Analisis kesesuaian antara aktivitas terhadap fasilitas rekreasi di ruang limpah sungai, Waduk Brigif, Kota Jakarta Selatan - Arthur Wira Yudha; Utami, Ni Wayan F. (Jurnal Arsitektur Lansekap, 2026)
Green Open Spaces (GOS) play an important role as multifunctional areas that support community recreational activities by providing public facilities. However, a mismatch between activity patterns and existing facilities can hinder their optimal use. This study was conducted at Ruang Limpah Sungai (RLS), Waduk Brigif, South Jakarta, to analyze the alignment between visitor activity patterns and available facilities. A quantitative descriptive method using an Importance-Performance Analysis (IPA) approach was applied, drawing on field observations, questionnaires, and literature review. The findings show that the jogging track and amphitheater are priority facilities requiring improvement and evaluation. The jogging track needs enhancement in responsiveness, security, and communication, while the amphitheater requires improvements in tangible, user understanding, and accessibility. Recommendations are presented as spatial concepts focusing on pavement materials, seating, inclusive facilities for people with disabilities, and sanitation. This study concludes that implementing responsive, inclusive, and user-oriented landscape design is essential to optimize the function of GOS as spaces for recreation, sports, and social interaction.